The Phenomeneon of Mass - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2020)
The concept of mass is one of the most fundamental in the whole of physics. Here it is shown that every mass is temporal, i.e. a mass could not exist without the flow of time. The close connection between mass and time is examined in more detail. This connection is used to prove that the special theory of relativity is wrong. Furthermore, mass is considered in relation to its gravitational effect. In the two-mass system, the change in the energy of the gravitational field when a mass moves is described. In the end, the connection between universal mass decay and gravity is established.